Identification of Essential Oils with Strong Activity against Stationary Phase Borrelia burgdorferi - Jie Feng; Wanliang Shi; Judith Miklossy; Genevieve M. Tauxe; Conor J. McMeniman; Ying Zhang (MDPI AG, 2018)
Lyme disease is the most common vector borne-disease in the United States (US). While the majority of the Lyme disease patients can be cured with 2–4 weeks antibiotic treatment, about 10–20% of patients continue to suffer from persisting symptoms. While the cause of this condition is unclear, persistent infection was proposed as one possibility. It has recently been shown that B. burgdorferi develops dormant persisters in stationary phase cultures that are not killed by the current Lyme antibiotics, and there is interest in identifying novel drug candidates that more effectively kill such forms. We previously identified some highly active essential oils with excellent activity against biofilm and stationary phase B. burgdorferi. Here, we screened another 35 essential oils and found 10 essential oils (Allium sativum L. bulbs, Pimenta officinalis Lindl. berries, Cuminum cyminum L. seeds, Cymbopogon martini var. motia Bruno grass, Commiphora myrrha (T. Nees) Engl. resin, Hedychium spicatum Buch.-Ham. ex Sm. flowers, Amyris balsamifera L. wood, Thymus vulgaris L. leaves, Litsea cubeba (Lour.) Pers. fruits, Eucalyptus citriodora Hook. leaves) and the active component of cinnamon bark cinnamaldehyde (CA) at a low concentration of 0.1% have strong activity against stationary phase B. burgdorferi. At a lower concentration of 0.05%, essential oils of Allium sativum L. bulbs, Pimenta officinalis Lindl. berries, Cymbopogon martini var. motia Bruno grass and CA still exhibited strong activity against the stationary phase B. burgdorferi. CA also showed strong activity against replicating B. burgdorferi, with a MIC of 0.02% (or 0.2 μg/mL). In subculture studies, the top five essential oil hits Allium sativum L. bulbs, Pimenta officinalis Lindl. berries, Commiphora myrrha (T. Nees) Engl. resin, Hedychium spicatum Buch.-Ham. ex Sm. flowers, and Litsea cubeba (Lour.) Pers. fruits completely eradicated all B. burgdorferi stationary phase cells at 0.1%, while Cymbopogon martini var. motia Bruno grass, Eucalyptus citriodora Hook. leaves, Amyris balsamifera L. wood, Cuminum cyminum L. seeds, and Thymus vulgaris L. leaves failed to do so as shown by visible spirochetal growth after 21-day subculture. At concentration of 0.05%, only Allium sativum L. bulbs essential oil and CA sterilized the B. burgdorferi stationary phase culture, as shown by no regrowth during subculture, while Pimenta officinalis Lindl. berries, Commiphora myrrha (T. Nees) Engl. resin, Hedychium spicatum Buch.-Ham. ex Sm. flowers and Litsea cubeba (Lour.) Pers. fruits essential oils all had visible growth during subculture. Future studies are needed to determine if these highly active essential oils could eradicate persistent B. burgdorferi infection in vivo.